On Fuzzy Measure on Fuzzy sets - F. Al-Mayahi, Noori; S. Hamzah, Karrar (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper, we study the fuzzy measure on fuzzy sets and prove some new properties.